Treating depression in an outpatient setting: Predictors of patient response to bouldering psychotherapy, cognitive behavioural therapy or exercise alone - Luttenberger, Katharina; Donath, Carolin; Grässel, Elmar; Kornhuber, Johannes; Schlüter, Annika; Dorscht, Lisa; Kind, Leona (Clinical Psychology & Psychotherapy, 2023)
Background: Bouldering psychotherapy (BPT) for depression has proven effective, but nothing is known about its potential predictors of response. This study should identify predictors of response to BPT, cognitive behavioural therapy (CBT) and an active control (home-based exercise programme; EP) using a literature-based model. Methods: In a multicentre randomised controlled trial, 233 outpatients were assigned to BPT, CBT or EP. Response (reduction of at least 46% on the Montgomery–Åsberg Depression Rating Scale [MADRS]) and remission (≤7 MADRS points) were defined as suggested by the literature. Predictors of response were identified twofold: (1) univariate analyses followed by logistic regression analyses in each group with all predictors yielding a univariate p-value <.20 and (2) a backward regression analysis with all potential predictors. Only variables that emerged as predictors in both types of analyses were interpreted. Results: There was a significantly greater proportion of responders (p =.035) in the BPT than in the EP. The chance of response in the BPT was higher for patients with a higher health-related quality of life. In the EP, response was higher for patients with lower interpersonal sensitivity, suffering from their first episode and living with a partner. Conclusions: Response rates in BPT are similar to or even higher than in other outpatient psychotherapy group therapies. BPT and CBT are suitable for a wide range of patients, but patients with higher functionality could start with psychoeducation and exercise.
CRIS-Team Scopus Importer:2023-09-15
Keywords: bouldering; cognitive behavioural therapy; depression; exercise; group psychotherapy; psychotherapy